Rheometry-on-a-chip: measuring the relaxation time of a viscoelastic liquid through particle migration in microchannel flows. Issue 3 (1st December 2014) - Del Giudice, Francesco; D'Avino, Gaetano; Greco, Francesco; De Santo, Ilaria; Netti, Paolo A.; Maffettone, Pier Luca
Abstract : A novel method to estimate the relaxation time of viscoelastic fluids, down to milliseconds, is here proposed. Abstract : A novel method to estimate the relaxation time of viscoelastic fluids, down to milliseconds, is here proposed. The adopted technique is based on the particle migration phenomenon occurring when the suspending viscoelastic fluid flows in microfluidic channels. The method is applied to measure the fluid relaxation times of two water–glycerol polymer solutions in an ample range of concentrations. A remarkable improvement in the accuracy of the measure of the relaxation time is found, as compared with experimental data obtained from shear or elongational experiments available in the literature. Good agreement with available theoretical predictions is also found. The proposed method is reliable, handy and does not need a calibration curve, opening an effective way to measure relaxation times of viscoelastic fluids otherwise not easily detectable by conventional techniques.